Amylovis-201 is a new dual-target ligand, acting as an anti-amyloidogenic compound and a potent agonist of the σ1 chaperone protein - Laura García-Pupo; Lucie Crouzier; Alberto Bencomo-Martínez; Johann Meunier; Axelle Morilleau; Benjamin Delprat; Marquiza Sablón Carrazana; Roberto Menéndez Soto del Valle; Tangui Maurice; Chryslaine Rodríguez-Tanty (Elsevier, 2024)
The aggregation of Amyloid-β (Aβ) peptides is associated with neurodegeneration in Alzheimer's disease (AD). We previously identified novel naphtalene derivatives, including the lead compound Amylovis-201, able to form thermodynamically stable complexes with Aβ species, peptides and fibrils. As the drug showed a chemical scaffold coherent for an effective interaction with the σ1 receptor chaperone and as σ1 agonists are currently developed as potent neuroprotectants in AD, we investigated the pharmacological action of Amylovis-201 on the σ1 receptor. We report that Amylovis-201 is a potent σ1 agonist by several in silico, in vitro and in vivo assays and that its anti-amnesic and neuroprotective effects involve a pharmacological action at σ1 receptors. Furthermore, we show for the first time that classical σ1 receptor agonist (PRE-084), and antagonist (NE-100) are able to interact and disaggregate Aβ25-35 fibrils. Interestingly, Amylovis-201 was the only compound inhibiting Aβ25-35 aggregates formation. Our results therefore highlight a dual action of Amylovis-201 as anti-aggregating agent and σ1 receptor agonist that could be highly effective in long-term treatment against neurodegeneration in AD.